Foreign economic priorities of Ukraine in the global chemical industry market - Zvarych, Roman; Demianiuk, Olga; Pochynok, Natalia (Herald of Economics, 2023)
Introduction. In the modern world, where globalization and international interaction are essential components of economic development for countries, the relevance of examining Ukraine’s foreign economic priorities in the global chemical industry market becomes particularly pronounced. The chemical industry is defined not only as a key sector of the economy but also as a strategic player in shaping the competitiveness and stability of the country on the international stage. Ukraine, with significant potential in the chemical sector, should carefully study and adapt its foreign economic strategies to effectively utilize this potential in the global market. Ensuring sustainable export growth, creating an attractive investment climate, and fostering innovative development in the chemical sphere become priorities that define the further path of development for Ukraine. Research Objective. The aim of the study is the systematic examination and analysis of the foreign economic priorities of the Ukrainian chemical industry in the global market, with the purpose of developing recommendations for improving the strategy of foreign economic activities in this sector. Methods. The study employs economic-statistical analysis to examine the dynamics of chemical product exports to different countries based on the geopolitical situation. Additionally, general scientific and empirical approaches, as well as tools from the field of economic science, are utilized. Methods such as synthesis, comparison, aggregation, and grouping are also applied to enhance the comprehensiveness of the research. Results. The study has explored trends in the global chemical industry market. The dynamics of value indicators for the export and import of the domestic chemical sector have been analyzed. Recommendations have been substantiated regarding the enhancement of competitiveness and export potential of Ukraine’s chemical industry in the context of globalization in the world economy. Perspectives for further research lie in examining specific segments of Ukraine’s chemical industry (pharmaceutical, petrochemical, etc.) with a focus on enhancing their competitiveness in external markets. This targeted exploration can provide valuable insights into the unique challenges and opportunities within each sector, paving the way for more refined and effective strategies to bolster their competitiveness globally.